A Developmental Study of Junior High School Mathematics Instructional Media Guided from Humanity-Value of Learning Model (MPNK) to Prevent Juvenile Delinquency - I Nyoman Murdiana; Rita Lefrida (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2017)
The Research and Development study aimed to develop a instructional media for math lesson using valid, practical, and effective humanity-value teaching model to prevent juvenile delinquency. To achieve the objective, the prototypical study was conducted using 3 phase development, namely (1) early assessment phase or front-end analysis, (2) the development phase consisting of expert validation and tryout I, and (3) the evaluation phase through tryout II using a quasi experiment design with anacova data analysis. The result from the first year development (2015) was the instructional media for junior high school using a valid humanity-value teaching model to prevent various kinds of juvenile delinquency. The products developed from the current research were in the form of lesson plan, teacher’s book, student book, and student worksheets. The products were in the form of draft of the instructional set which was valid.